2013
DOI: 10.1590/s0102-86502013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study and histomorphometric analysis of bone allografts lyophilized and sterilized by autoclaving, gamma irradiation and ethylene oxide in rats

Abstract: PURPOSE:To compare three sterilization methods (autoclave, gamma irradiation and ethylene oxide) over non demineralized lyophilized bone allografts. METHODS:Bone allografts were implanted on paravertebral muscles of 21 rats. After 30 days animals were sacrificed and grafts underwent comparative analysis regarding histomorphometric and macroscopic parameters. RESULTS:Allografts that underwent the three sterilization methods presents similar weight gain, cortical thickness similar to control group, and less fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Furthermore, as gamma irradiation is widely used within the food (i.e., at low doses, usually < 5 kGy) and healthcare (i.e., for sterilization, usually at doses > 25 kGy) industries, many reports are available on the influence of the sample processing conditions, sample matrix, and sample conditioning on various sample parameters [44][45][46][47][48]. Specifically, extensive comparative studies and characterization experiments are usually performed when developing novel therapeutic products requiring sterility, as the retained method may drastically alter key and critical product attributes [49][50][51][52]. It is, therefore, highly advisable to consider sterility requirements and validation steps early on in the prototype development phase for sparing use of resources and augmentation of the technical chances of successful development.…”
Section: Effects Of Gamma Irradiation On the Proteome Of Stabilized P...mentioning
confidence: 99%
“…Furthermore, as gamma irradiation is widely used within the food (i.e., at low doses, usually < 5 kGy) and healthcare (i.e., for sterilization, usually at doses > 25 kGy) industries, many reports are available on the influence of the sample processing conditions, sample matrix, and sample conditioning on various sample parameters [44][45][46][47][48]. Specifically, extensive comparative studies and characterization experiments are usually performed when developing novel therapeutic products requiring sterility, as the retained method may drastically alter key and critical product attributes [49][50][51][52]. It is, therefore, highly advisable to consider sterility requirements and validation steps early on in the prototype development phase for sparing use of resources and augmentation of the technical chances of successful development.…”
Section: Effects Of Gamma Irradiation On the Proteome Of Stabilized P...mentioning
confidence: 99%
“…All the sponges presented a similar elliptical shape and a smooth, soft and sponge-like morphology along with thickness of 2 mm and wide length of ~7 mm. These uniform elliptical shapes can be ascribed to the 3 h refrigeration, freeze-drying and lyophilization [18]. Figure 2 showed the (a) FTIR spectra, (b) compressive strength, and (c) porosity of bare DC/HAp and 1, 5 and 10 μM EGCG/DC/HAp sponges.…”
Section: Discussionmentioning
confidence: 98%
“…Mat-Salleh et al used discarded bone fragments from hip arthroplasty as samples and found that 0.5% chlorhexidine was significantly superior to povidone-iodine and alcohol in disinfecting contaminated bone ( 20 ). Some researchers analyzed the histomorphology of rat allografts after sterilization with high-pressure sterilization, gamma irradiation, and ethylene oxide and found no significant differences among the three groups ( 21 ). Mortazavi et al ( 22 ) conducted a systematic review of the literature on contamination related to bone transplantation and found that the contamination rate of dislodged bone tissue during surgery was close to 40%.…”
Section: Discussionmentioning
confidence: 99%